Scorpion Envenomation: The Cause of Inadequate Subarachnoid Block - A Case Series - Pakhare, Vandana Patilbuwa; Nanda, Ananya; Priyanka, Reddy Devi Sai; Gopinath, Ramchandran (Faculty of Medicine, Brawijaya University, 2023)
Background: Failure of neuraxial or regional anaesthesia can result from factors such as drug errors, technical inefficiencies, and poor patient positioning. While these causes are well-known, resistance to local anaesthetic action due to mutations in sodium channels or scorpion sting is a lesser-known contributor to block failure. In India, a tropical country with a significant number of patients presenting for surgical procedures, a history of scorpion bites is not uncommon.Case: We observed seven cases of failed regional anesthesia who had history of scorpion sting. All the patients received intrathecal bupivacaine by experienced anesthesiologists, of seven patients five patients did not develop sensory or motor block. One patient had delayed successful subarachnoid block after second attempt and one patient had successful block at first attempt.Conclusion: Our observations revealed instances of failed spinal blocks, despite adequate drug dosages and experienced anesthesiologists performing the procedures, in patients with a history of scorpion envenomation. Accordingly, our study concludes that obtaining a thorough scorpion sting history during pre-anesthesia check-ups, particularly in endemic areas, can effectively prevent unnecessary repeated pinpricks, escalating dosages, patient and surgeon discomfort, and skepticism towards the skills of anesthesiologists.